(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This study aims to analyze the economic and social impacts of the maritime jihad movement on Western Algeria during the sixteenth century, highlighting its effects on social structure and regional economic development. It adopted a descriptive and analytical methodology based on original historical sources, archival documents, and accounts from diverse historians, with a focus on the sixteenth century and using the city of Algiers, its fleet, and population as the primary sample. The study employed historical research tools, as well as quantitative and statistical analysis of booty, ships, and captives. Results showed that maritime jihad was a cornerstone of economic growth through the influx of spoils, tributes, and utilization of captives, leading to economic prosperity, demographic expansion, and notable population diversity. It further contributed to urban development and the flourishing of crafts and culture, while also deepening practices of slavery and social disparities within society.